MASS THERAPEUTIC EDUCATION FOR MONITORING SUICIDAL BEHAVIOR IN COMMUNITY - Fadhillah Salman Sofyan (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2021)
Background: Suicide is a worrying problem in Indonesia because of increase in case reported. There has been an increase in suicide rates both globally and in Indonesia. The negative stigma, lack of education, and lack of understanding of the role of the community make it difficult to reduce the number of suicides. This study aims to discuss mass therapeutic education for monitoring suicidal behavior in community.Method: Researchers used 15 journals and literature that discuss the impact and vulnerability of distance learning on students' mental health conditions. Â Conclusion: The role of society in reducing the suicide rate is very much needed. The community can help make early detection of suicide. Society can help prevent suicidal ideas from arising in those around them. The public can provide information to the authorities and give advice for suicide perpetrators to visit a health center. The role of the community can be integrated in a structured and neat system that can make suicide prevention efforts becme optimal.